A new heuristic method to solve straight assembly line balancing problem - Mohd Ariffin, Mohd Khairol Anuar; Fathi, Masood; Ismail, Napsiah (Universiti Putra Malaysia Press, 2012)
Assembly line balancing is well-known in mass production system but this problem is non-deterministic polynomial-time(NP)-hard, even for a simple straight line. Although several heuristic methods have been introduced and used by researchers, knowing and using an effective method in solving these types of problems in less computational time have a considerable place in the area of line balancing problem. In this research, a new heuristic approach, known as critical node method (CNM), was introduced and tested by solving several test problems available in the literature so as to solve straight assembly lines. Finally, the obtained results are compared with 9 other heuristic rules in some performance measures. Thus, it is concluded that the proposed CNM is better than the rest in all the measures.